Bipolar radiofrequency ablation creates different lesion characteristics compared to simultaneous unipolar ablation. (13th October 2019) - Nguyen, Duy T.; Zheng, Lijun; Zipse, Matthew M.; Borne, Ryan T.; Tzou, Wendy S.; Fleeman, Blake; Sauer, William H.
ABSTRACT: Introduction: Both bipolar and simultaneous radiofrequency ablation (bRFA, simRFA) have been used to treat thick midmyocardial substrate as well as during circular, multipolar ablation between shorter distances. Objectives: We sought to evaluate the biophysical parameters of simRFA, sequential unipolar RFA (seqRFA), and bRFA. Methods: Bovine myocardium was placed in a circulating saline bath. To simulate thick substrate conditions, two open irrigated ablation catheters were oriented across from each other, with myocardium in between. Thermocouples were placed in the center, ±2 mm, of the myocardium. Unipolar ablations were performed sequentially or simultaneously at 50 W for 60 seconds and compared to bRFA using the same settings. In addition, to simulate multipolar ablation, two open irrigated ablation catheters were oriented on the same side and perpendicular to myocardium at 1, 2, and 4 mm spacing. SimRFA were performed at 15 and 25 W for 60 seconds and compared to bRFA. Results: For thicker tissue, simRFA produced similar lesion volume and depth compared to bRFA but with a lesion geometry similar to seqRFA. Unlike seqRFA and simRFA, bRFA had a necrotic core spanning the myocardium. Core depths, volumes, and temperatures were significantly greater for bRFA lesions compared to simRFA or seqRFA (Figure, P  < .001). Similar results were consistent for bRFA and simRFA at shorter spacings. Conclusions: BRFA has greater core lesion temperatures, corresponding to a denser and larger necrotic core, than either simRFA or seqRFA. This may have implications for considering the optimal strategy for deep midmyocardial substrates or during multipolar ablation.